A traditional ground-based system for woody biomass harvesting in Short Rotation Woody Crop (SRWC) plantations – a case study in Michigan. Issue 1 (2nd January 2017) - Carter, Zach; Pan, Fei; Lin, Yingqian; Miller, Raymond O.; Srivastava, Ajit
ABSTRACT: Reconfigured forage harvesting equipment utilized for plantation biomass harvesting and processing is highly productive but is expensive and not yet widely used in short rotation woody crop (SRWC) production systems. Traditional timber harvesting equipment, on the other hand, has been widely used for decades and can be adapted for use in SRWC plantations. Productivity of these traditional systems is not well understood when utilized in such plantations. To that end, productivity and costs were evaluated for a traditional ground-based system (feller-buncher, skidder, loader, and grinder) in a 3.1-ha small-diameter hybrid poplar plantation in Escanaba, Michigan, USA. Operation cycle time predictive models were developed from a time and motion analysis. Operation productivity and costs were generated and then compared with published data for a reconfigured forage harvesting system. Compared values between the two systems included: machine hourly rate, in dollars per scheduled machine hour (/SMH), the production cost, in dollars per oven dry ton (/ODT), and the system production rate, in oven dry tons per productive machine hour (ODT/PMH). The machine hourly rate and production cost of the traditional system were found to be 284.00/SMH, and 22.30/ODT, respectively; while the production rate was found to be variably between 8.82–35.44 ODT/PMH. A sensitivity analysis was conducted on the traditional harvesting system to test the effect of machine utilization on production costs, where an equal utilization rate of 80% dropped production costs to 17.92/ODT. A net energy analysis was also conducted, demonstrating a net energy ratio of 24.8:1 for the traditional system.